Cardiac arrest and resuscitation activates the hypothalamic-pituitary-adrenal axis and results in severe immunosuppression. Issue 5 (May 2021) - Zhao, Qiang; Shen, Yuntian; Li, Ran; Wu, Jiangbo; Lyu, Jingjun; Jiang, Maorong; Lu, Liping; Zhu, Minghua; Wang, Wei; Wang, Zhuoran; Liu, Qiang; Hoffmann, Ulrike; et al.
In patients who are successfully resuscitated after initial cardiac arrest (CA), mortality and morbidity rates are high, due to ischemia/reperfusion injury to the whole body including the nervous and immune systems. How the interactions between these two critical systems contribute to post-CA outcome remains largely unknown. Using a mouse model of CA and cardiopulmonary resuscitation (CA/CPR), we demonstrate that CA/CPR induced neuroinflammation in the brain, in particular, a marked increase in pro-inflammatory cytokines, which subsequently activated the hypothalamic-pituitary-adrenal (HPA) axis. Importantly, this activation was associated with a severe immunosuppression phenotype after CA. The phenotype was characterized by a striking reduction in size of lymphoid organs accompanied by a massive loss of immune cells and reduced immune function of splenic lymphocytes. The mechanistic link between post-CA immunosuppression and the HPA axis was substantiated, as we discovered that glucocorticoid treatment, which mimics effects of the activated HPA axis, exacerbated post-CA immunosuppression, while RU486 treatment, which suppresses its effects, significantly mitigated lymphopenia and lymphoid organ atrophy and improved CA outcome. Taken together, targeting the HPA axis could be a viable immunomodulatory therapeutic to preserve immune homeostasis after CA/CPR and thus improve prognosis of post-resuscitation CA patients.